2011
DOI: 10.1002/ejoc.201100270
|View full text |Cite
|
Sign up to set email alerts
|

A New and Efficient Procedure for Bi(OTf)3‐Promoted [3+2] Cycloaddition of N‐Tosylaziridines to Yield Imidazolines

Abstract: [3+2] Cycloaddition of a series of substituted N‐tosylaziridines with various nitriles promoted by Bi(OTf)3 is described for the synthesis of substituted imidazolines under mild reaction conditions. The procedure works well over a range of substrates to give the corresponding products in good to excellent yields (up to 99 %).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 46 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…Li et al reported a Lewis acid-mediated [3 + 2]cycloaddition reaction of N-tosylaziridines (315) with nitriles (316) to synthesize 2-imidazolines (317) (Scheme 89). [87] After the initial Lewis acid screening, Bi(OTf) 3 was found to be a suitable reagent to execute the synthesis. With different aromatic-substituted (R 1 = aryl) aziridines (315), the imidazolines were isolated in good to excellent yields (up to 99%).…”
Section: Methods E: Synthesis Of Imidazolines From Aziridinesmentioning
confidence: 99%
“…Li et al reported a Lewis acid-mediated [3 + 2]cycloaddition reaction of N-tosylaziridines (315) with nitriles (316) to synthesize 2-imidazolines (317) (Scheme 89). [87] After the initial Lewis acid screening, Bi(OTf) 3 was found to be a suitable reagent to execute the synthesis. With different aromatic-substituted (R 1 = aryl) aziridines (315), the imidazolines were isolated in good to excellent yields (up to 99%).…”
Section: Methods E: Synthesis Of Imidazolines From Aziridinesmentioning
confidence: 99%
“…Formal [119,120], Sc(OTf) 3 [121], Bi(OTf) 3 [122], etc., have been utilized for this transformation. Recently, a regioselective synthesis of 4-(trifluoromethyl)-1,3- …”
Section: Synthesis Of Imidazolidines Imidazolines and Imidazolesmentioning
confidence: 99%
“…A Bi(OTf) 3 ‐mediated direct synthesis of imidazolines starting from aliphatic or aromatic nitriles and N ‐tosylaziridines was developed . An extensive screening of reaction conditions indicated that the reactions could be performed, but with lower yields, with other Lewis acids such as ZnCl 2 , Sm(OTf) 3 , In(OTf) 3 or ZrCl 4 .…”
Section: Activation Of Nitrogen‐containing Functionsmentioning
confidence: 99%